Peran Tenaga Kependidikan Dalam Pengembangan Unit Pendidikan Unggulan Fakultas Peternakan, Institut Pertanian Bogor - Lanjarsih Lanjarsih; Musa Hubeis; Farid M. Afandi (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2018)
The high levels of motivation, compensation, organizational culture, and competence of educational personnel greatly affect their performance. As the motivation, compensation, organizational culture and competence of the educational personnel of Faculty of Animal Science Bogor Agricultural University (IPB) in achieving the performance has still not been optimal, this research aimed to analyze the factors affecting the performance of the educational personnel in the Faculty of Animal Science Bogor Agricultural University (IPB), both directly and indirectly i.e. to analyze the effect of compensation on motivation, to analyze the effect of compensation on organizational culture, in which motivation serves as intervening variable, to analyze the effect of compensation on competence, in which organizational culture serves as the intervening variable, and to analyze the effect of motivation on competence. The variables include motivation, compensation, organizational culture, and competence of the academic personnel. The data collection technique was conducted by doing interviews and distributing questionnaires using the Likert scale. The reliability on the data obtained, descriptive analysis and Structural Equation Model (SEM) analysis were utilized. Based on the research results, it is revealed that the compensation variable has a significant effect on the motivation, while the compensation has no significant effects on the organizational culture in which the motivation serves as intervening variable. Thus, compensation has no significant effects on the competence in which the organizational culture serves as intervening variable, and motivation also has no significant effect on the competence.Keywords: motivation, compensation, organization culture and competence, PLSAbstrak: Tinggi rendahnya motivasi, kompensasi, budaya organisasi dan kompetensi tenaga kependidikan sangat memengaruhi kinerja. Penelitian dilakukan karena motivasi, kompensasi, budaya organisasi serta kompetensi tenaga kependidikan Fakultas peternakan Institut Pertanian Bogor (IPB) dalam pencapaian kinerja masih belum optimal. Tujuan penelitian ini adalah untuk menganalisis faktor-faktor yang memengaruhi kinerja tenaga kependidikan di Fakultas Peternakan IPB baik secara langsung maupun tidak langsung, yaitu menganalisis pengaruh kompensasi terhadap motivasi, menganalisis pengaruh kompensasi terhadap budaya organisasi, dimana motivasi sebagai peubah intervening, menganalisis pengaruh kompensasi terhadap kompetensi dimana budaya organisasi sebagai peubah intervening, menganalisi pengaruh motivasi terhadap kompetensi. Peubahnya adalah motivasi, kompensasi, budaya organisasi dan kompetensi Tendik. Teknik pengumpulan data adalah dengan interview serta kuesioner menggunakan skala Likert. Peneliti menggunakan reabilitas terhadap data yang diperoleh dan selanjutnya menggunakan analisis deskriptif dan analisis Struktural Equation Model (SEM). Dari hasil penelitian diketahui peubah kompensasi berpengaruh nyata terhadap motivasi, kompensasi terhadap budaya organisasi dimana motivasi sebagai intervening tidak berpengaruh nyata, kompensasi tidak berpengaruh nyata terhadap kompetensi dimana budaya ornagisasi sebagai intervening dan motivasi tidak berpengaruh nyata terhadap kompetensi. Kata kunci: motivasi, kompensasi, budaya organisasi dan kompetensi, PLS